British Social Attitudes: Continuity and Change Over Two Decades 2003
DOI: 10.4135/9781849208628.n5
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Crisis of Political Participation?

Abstract: There appears to be a crisis of political participation in Britain. Turnout at the last UK general election was, at 58 per cent, lower than at any other general election since 1918. Moreover, voters have been reluctant to go to the polls in every other kind of election held over the last six years. Unsurprisingly, then, politicians of all political persuasions have been asking themselves how they can 're-engage' the public with the political process.This decline in electoral participation might seem particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…In turn, the unequal participation in community activities is influenced by a range of socio-economic factors, particularly educational background but also economic status (Curtice andSyed, 2003, Parry et al, 1992). In this context, the most marginalised groups tend to be the working class and the young (Warde et al, 2003).…”
Section: Equitymentioning
confidence: 99%
“…In turn, the unequal participation in community activities is influenced by a range of socio-economic factors, particularly educational background but also economic status (Curtice andSyed, 2003, Parry et al, 1992). In this context, the most marginalised groups tend to be the working class and the young (Warde et al, 2003).…”
Section: Equitymentioning
confidence: 99%
“…Despite considerable similarities, the prominence of social capital in the UK has not experienced the same decline as the USA (Johnston and Jowell, 2001;Hall, 2002, Curtice andSeyd, 2003;Pattie et al, 2004). Reasons include the significantly expanded access to higher education and government action supporting community involvement (Hall, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…There has been much sympathy with Inglehart's (1990) thesis that a post-material culture is developing, with citizens now more interested in issues of identity and lifestyle. It is frequently suggested that there has been a decline and/or fragmentation of class politics and trade union membership (Curtice and Seyd, 2003). Citizen engagement has become increasingly issue-led rather than ideologically driven.…”
Section: Jamesmentioning
confidence: 99%